Metastable defects in proton implanted and annealed silicon - Jelinek, M.; Laven, J. G.; Ganagona, N.; Job, R.; Schustereder, W.; Schulze, H. J.; Rommel, Mathias; Frey, Lothar (Solid State Phenomena, 2016)
Two metastable defects with energy levels at Ec-0.28eV and Ec-0.37eV, which previously have been reported in proton implanted- and in proton implanted and annealed crystalline silicon are discussed. Recent results on the peculiar behavior of these defects upon periodical application of two different bias conditions during DLTS measurement are reviewed. Two specifically designed DLTS measurement sequences are proposed in order to further reveal the defects transformation rates and respective activation energie
UnivIS-Import:2016-06-01:Pub.2016.tech.IE.LEB.metast
Keywords: Crystalline silicon; Metastable defects; Proton implantation